h - Jiang, Tianzi; Navab, Nassir; Pluim, Josien P. W.; Viergever, Max A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The three-volume set LNCS 6361, 6362 and 6363 constitutes the refereed proceedings of the 13th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2010, held in Beijing, China, in September 2010. Based on rigorous peer reviews, the program committee carefully selected 251 revised papers from 786 submissions for presentation in three volumes. The third volume includes 83 papers organized in topical sections on segmentation and modeling, robotics, motion modeling and computer-assisted interventions, image reconstruction, enhancement and representation, and computer-aided diagnosis.
Segmentation and Modeling -- Robotics, Motion Modeling and Computer-Assisted Interventions -- Image Reconstruction, Enhancement and Representation -- Computer Aided Diagnosis.
Keywords: Computer science; Computer simulation; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Simulation and Modeling